Instability of the solution of the problem on determining the reentry time of satellites on elliptic orbits. (October 2019) - Nazarenko, А.I.; Usovik, I.V.
Abstract: The article considers specific examples, which show that the solution of the problem on determining the reentry time of elliptic-orbit satellites can be unstable. An analysis is executed on the basis of orbital data about reentry of two satellites: Molnija-1-44 and Zenit-2SB second stage. The presence of photos during their reentry and application of the improved methodology for updating of orbital parameters on measurements allowed to get more reliable results. Highlights: Relative errors for calculation of SC reentry are equals ≈15% of remaining lifetime. Source of errors is unpredictable atmospheric density variations on interval. It is impossible to increase accuracy with existing models of atmospheric density. OFM ensures increasing accuracy of current drag determination as compared to LST. As a result, drag determination accuracy of several % of current level is achieved.